(untitled) (Periphērica, 2023)
This article analyzes two novels by the Spanish feminist Concepción Gimeno in Mexico —Suplicio de una coqueta (1885) and Maura (1888)—, given the Cuban nationality of their protagonists. These texts are contrasted with her first novel, published in Spain: Victorina o heroísmo del corazón (1873). The article describes the way in which Cuba is appropriated by the discourse to address two issues: the future of the Spanish nation, and that of Hispanic world/Latin race. Regarding the latter, according to Gimeno, Porfirian Mexico is expected to exercise its continental leadership. In this Regenerationist debate, Cuba becomes a symbolic object of study for the rationalist eugenics discourse of late 19th century.